Borrowing morphology: The influence of Russian on the Veps system of indefinite pronouns - Karjalainen, Heini (Uralica Helsingiensia, 2019)
Veps is a Finnic minority language that has long been influenced by Russian, the prestige language in the speech area. The influence of Russian can be perceived in all subsystems of the Veps language, but hardly any research has been done on its impact on morphology. The current paper focuses on the influence of Russian on the Veps indefinite pronouns and their restructuring. The contemporary Veps indefinite pronoun system is based on the use of different affixes and particles, i.e., indefiniteness markers, which are attached to interrogative stems. This article describes the various Veps indefiniteness markers, which have been acquired via morpheme transfer (MAT) and morphological pattern transfer (PAT) from Russian. The borrowing of indefiniteness markers is typical for languages under the very strong influence of another language. According to contemporary studies, the motivation for borrowing should primarily be attributed to sociolinguistic factors and less to structural-typological similarities of the languages in question. In the Veps language community, such sociolinguistic factors are the minority status of the Veps language and the bilingualism of its speakers.